Efeito da natação e da corrida sobre a qualidade seminal - Nesello, Leonardo Monteiro (My University, 2020)
Significant changes in semen quality may occur due to the practice of physical activity, which can alter its quality according to the type of physical activity, intensity and duration. This relationship is especially important because of the fact that physical activity has become widely popular worldwide. In addition, the incidence of couple´s infertility in the world is around 8 to 15%, and in up to 50% of the cases the cause of infertility is male. The goal of this study was to verify the effect of the physical activity of the swimming and of the running, on a moderate form, on seminal quality. A control group, formed by healthy individuals practicing low intensity physical activity, was used in the comparison between the groups. This is a cross-sectional study performed with healthy men practicing moderate physical activity. The seminal parameters of 39 men between the ages of 23 and 37 years were evaluated. The level of physical activity was evaluated by calculating the metabolic equivalents (METs), using the Compendium of Physical Activities (CPA) to identify the intensities. Seminal parameters of volume, concentration/ml, total concentration, progressive motility, total motility, and sperm morphology were evaluated according to the normal values recommended by the World Health Organization (WHO) (2010). For the descriptive statistics of the continuous variables, the mean and the standard deviation were calculated, while for the inferential analysis the normality of the data was evaluated using the Shapiro-Wilk test for all dependent variables. When normality was confirmed, analysis of variance (ANOVA) was used to compare the groups for the descriptive variables. For all the statistical tests, a p< 0.05 was considered. The results did not show statistical differences between groups regarding semen volume, concentration/ml, total concentration, progressive motility and total motility. On the other hand, there is a statistical difference between the groups for sperm morphology. In addition, sperm morphology was below the 4% threshold established by WHO for the swimming and running group. In conclusion, we note that there are no differences in seminal parameters of men who practice different sports of moderate intensity, however sperm morphology can to be impaired with the practice of moderate physical activity.
Mudanças significativas na qualidade do sêmen podem ocorrer devido à prática de a intensidade e a duração. Essa relação é especialmente importante em virtude do fato de que a atividade física tornou-se amplamente popular no mundo inteiro. Além disso, a prevalência de infertilidade conjugal no mundo gira em torno de 8 a 15% e, em até 50% dos casos, a causa da infertilidade é masculina. O presente estudo teve como objetivo verificar o efeito da atividade física da natação e da corrida, de forma moderada, sobre a qualidade seminal. Um grupo controle, formado por indivíduos saudáveis praticantes de atividade física de baixa intensidade, foi utilizado na comparação entre os grupos. Trata-se de um estudo transversal realizado com homens saudáveis praticantes de atividade física. Foram avaliados os parâmetros seminais de 39 homens contendo idades entre 23 a 37 anos. O nível de atividade física foi avaliado por meio do cálculo dos equivalentes metabólicos (METs), utilizando o Compêndio de Atividades Físicas (CAF) para identificar as intensidades. Os parâmetros seminais do volume, concentração/ml, concentração total, motilidade progressiva, motilidade total e morfologia dos espermatozoides foram avaliados conforme os valores normais preconizados pela Organização Mundial da Saúde (OMS) (2010). Para a estatística descritiva das variáveis contínuas, foram calculados a média e o desvio padrão enquanto que para a análise inferencial a normalidade dos dados for avaliada por meio do Teste de Shapiro-Wilk para todas as variáveis dependentes. Sendo comprovada a normalidade, a analise de variância (ANOVA) foi utilizada na comparação dos grupos. Para todos os testes foi adotado um p< 0,05. Os resultados não demonstraram diferenças estatísticas entre os grupos no que se refere ao volume do sêmen, concentração/ml, concentração total, motilidade progressiva e motilidade total. Por outro lado, existe uma diferença significativa entre os grupos para a morfologia espermática. Além disso, a morfologia espermática ficou abaixo do limiar de 4% estabelecido pela OMS para o grupo da natação e da corrida. Em conclusão, notamos que não existem diferenças nos parâmetros seminais de homens que praticam diferentes modalidades esportivas de intensidade moderada, no entanto a morfologia espermática pode ser prejudicada com a prática de atividade física moderada.
Keywords: Sêmen; Infecundidade; Exercícios físico; Semen; Infertility; Exercise